Emprego dos focos de calor na avaliação das áreas queimadas e em incêndios florestais em Paragominas, Pará, Brasil - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2019)
The number of occurrences of heat sources has increased in recent years in Brazil, showing a worrying perspective in occupation dynamics. Proper use of these monitoring data can support effective and coherent local management policies. Therefore, the objective of this study was to evaluate the use of heat source data on the burning dimension in the municipality of Paragominas, State of Pará, in the 2015-2016 cycle, in order to subsidize our understanding of fire recurrence and to provide a constructive perspective for fire prevention and combat to protect forest remnants and, consequently, ensure environmental quality. For this purpose, data from INPE’s Fire Database, remote sensing products and geoprocessing and image interpretation techniques were used to understand such particularities occurring in the period. The results showed a low coincidence of heat foci with a fire risk of over 50% on the mapped burned areas, around 20% in 2015 and 10% in 2016. On the other hand, they were important temporal indicators of the pressure zones to forest remnants, indicating, even, the occurrence in many of the agricultural settlements.
Use of heat foci in the evaluation of burned areas and of forest fires in Paragominas, Pará, Brazil
Keywords: Fogo; Focos de calor; Gestão territorial; Paragominas; CNPQ::CIENCIAS EXATAS E DA TERRA